Comparing the African American And Oromo Movements in the Global Context - Jalata, Asafa (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. A comparison of the causes, processes, and outcomes of the anticolonial struggles undertaken by the African-American movement in the U.S. and the Oromo movement in Ethiopia is presented. It is noted that both movements developed in opposition to colonial domination, a racial/ethnonational hierarchy, cultural repression and destruction, labor and economic exploitation, and the denial of individual and national rights; and in resistance to the capitalist world-system.